2017
DOI: 10.3390/ijms18061317
|View full text |Cite
|
Sign up to set email alerts
|

The Protease Inhibitor CI2c Gene Induced by Bird Cherry-Oat Aphid in Barley Inhibits Green Peach Aphid Fecundity in Transgenic Arabidopsis

Abstract: Aphids are phloem feeders that cause large damage globally as pest insects. They induce a variety of responses in the host plant, but not much is known about which responses are promoting or inhibiting aphid performance. Here, we investigated whether one of the responses induced in barley by the cereal aphid, bird cherry-oat aphid (Rhopalosiphum padi L.) affects aphid performance in the model plant Arabidopsis thaliana L. A barley cDNA encoding the protease inhibitor CI2c was expressed in A. thaliana and aphid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…This explains the finding that the expression changes of β-glucosidase were specifically induced in S. avenae feeding on wheat in our study. Some proteases, like serine proteases and cysteine proteases, have both digestive and defensive functions in insects [56,57]. In this study, some cysteine proteases showed specific expression in S. avene on wheat, whereas some serine proteases were found to be specifically induced by barley.…”
Section: Molecular Factors Underlying Aphids' Use Of Resistant Host Pmentioning
confidence: 52%
See 1 more Smart Citation
“…This explains the finding that the expression changes of β-glucosidase were specifically induced in S. avenae feeding on wheat in our study. Some proteases, like serine proteases and cysteine proteases, have both digestive and defensive functions in insects [56,57]. In this study, some cysteine proteases showed specific expression in S. avene on wheat, whereas some serine proteases were found to be specifically induced by barley.…”
Section: Molecular Factors Underlying Aphids' Use Of Resistant Host Pmentioning
confidence: 52%
“…Thus, the differential expression of these digestive enzymes may have significant implications in the adaptation of insect biotypes on different host plants with significant nutritional variation [52][53][54][55]. In addition to their nutritional implications, some proteases, such as the above-mentioned serine proteases, may also be involved in defensive adaptation against proteinase inhibitors of host plants for insects [56,57]. Indeed, proteinase inhibitors of wheat have been proved to have anti-metabolic effects on S. avenae midgut proteases [58].…”
Section: Divergence Of Aphid Biotypesmentioning
confidence: 99%
“…In addition, THIO1567 was at a lower expression in the antisense line compared to the control line upon GPA infestation ( Figure 5 ), and both THIO1567 and CI2c were found at a higher transcript abundance in the resistant wild barley Hsp5 than in the other genotypes ( Figure 1 ). The proteinase inhibitor, CI2c , was previously shown to inhibit GPA reproduction when expressed in Arabidopsis [ 36 ]. Thionins are sulfur-rich small proteins with in vitro toxicity against plant fungal pathogens and bacteria [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many transgenic plants expressing PIs from non-host and wild relatives are reported to counteract the insect pests (Abdeen et al, 2005;Dunse et al, 2010;Hamza et al, 2018;Macedo et al, 2015;Rehman et al, 2017). Therefore, a continuous screening of non-hosts and wild relatives is essential to identify effective ecofriendly PIs to target economically important insect pests such as Helicoverpa armigera and Achaea janata (Jamal et al, 2013;Losvik et al, 2017). Controlling H. armigera (a polyphagous pest) and A. janata (a major pest on Ricinus communis) has been a major challenge since they are efficient in overcoming defense mechanisms of host plant and chemical pesticides due to their broad host range and voracious feeding behaviour.…”
Section: Introductionmentioning
confidence: 99%